(3GdRjL GdTGeds - (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Ydi JhGJQ BdGFg hHYO , agPG RjL hVYJg Ydi ebJVi ChSGW UMMgG GdTjN CHh GdhaGA eMeO Hf CMeO GdHhRLGfi hCUMGHg , HCQUGO eJhGdjI hGeJMGfGJ UOQJ efge HYO QUO GdeCehf s
(3BNQgG (B:s
(3aJCNP ef eMjW GdOGFQI GdJi SHbJ HOGQ GdEfMQGa , hfUd ef WQag Edi eQcR GdOGFQI NWC fNQLg Ydi GdESJbGeI aYdjg GdbHdI , hGddg CYde HGdUhGH Je s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B464 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B839 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B969s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi s
Keywords: (3Gdadcs